The Effectiveness of the Actions of the General Election Supervisory Agency (Bawaslu) of Palangka Raya City in Handling Election Crimes: A Case Study of Double Voting Using Another Person’s Identity - Safitri, Laila; Aristoteles, Aristoteles; F Dewi, Yurika (Dinasti Research, 2025)
he occurrence of electoral fraud in Palangka Raya City was a direct finding by the General Election Supervisory Agency (Bawaslu) of Palangka Raya. The case involved the misuse of voting rights, specifically impersonating another person to vote, which constitutes a violation Article 533 of Law No. 7 of 2017 on General Elections. Upon discovering the incident, Bawaslu promptly referred the case to the police investigation team for further legal action. To prevent and address such issues, Bawaslu Palangka Raya has introduced an innovative public outreach program aimed at increasing community participation in election monitoring and preventing electoral violations. This study attempts to investigate the utilization of prevention and enforcement measures related to electoral violations and to identify the challenges in their execution. Using an empirical juridical method through observation, interviews, and online media data analysis, the research found that the implementation of prevention and enforcement efforts is not yet fully effective. Key obstacles include suboptimal inter-agency coordination, limited public awareness, and the constrained time frame for legal proceedings in handling election crimes. Currently, Bawaslu Palangka Raya’s innovation community outreach serves as a short-term solution. This study recommends strengthening supervision and improving inter-agency coordination, with more active communication and cooperation to enhance institutional capacity.